PENDUGAAN UMUR SIMPAN MINUMAN EKSTRAK BERAS HITAM DALAM KEMASAN METALIZED DENGAN PENDEKATAN ARRHENIUS - Afistia, Novalinda Rezty; ., Nurhidajah; Sya'di, Yunan Kholifatuddin (Jurnal Pangan dan Gizi, 2024)
Black rice extract instant drink is one of the innovative food products and good for health because of its high anthocyanin content. Instant drink products in powder form have high hygroscopicity properties. The transfer of moisture from the environment can cause deterioration during storage. Deterioration in quality can cause chemical, enzymatic reactions and physical changes in the product. This study aims to determine the water content, Aw, hygroscopicity and estimation of the shelf life of black rice extract drinks with temperature differences and storage duration. This research procedure involves packaging products using metalized  packaging and then storing at 3 different temperatures (27°C, 37°C, and 47°C) for 4 weeks. The longer the storage and the higher the storage temperature will cause an increase in moisture content, Aw, and hygroscopicity of black rice extract beverage products.  The shelf life of black rice extract drinks stored at 27°C reached 33.73 weeks (236.11 days), longer than storage at 37°C which was 16.64 weeks (116.47 days), and storage at 47℃ which only reached 8.54 weeks (58.80 days).